THE IMPACT OF ARTIFICIAL INTELLIGENCE ON THE LAW OF DELICT AND PRODUCT LIABILITY - Franaaz Khan (Obiter, 2024)
An enquiry into negligence involves evaluating a defendant’s conduct according to a standard that is acceptable to society. This standard is expressed with reference to a fictitious ‘reasonable person’ that represents society’s expectation of adequate and reasonable conduct in the law of delict. It represents an objective standard that all legal subjects must adhere to by paying sufficient attention to ensure that their conduct is in line with the standard of care that society expects. However, this test of negligence in delict would in the near future require reform as there has been the new era of Artificial Intelligence (AI) that has legal implications. AI a term that is unpacked further in this article has seen it already diagnosing diseases, drafting legal contracts, and providing different levels of service. What happens in instances where these AI systems cause harm? How should South African law respond to accidents caused by AI? It is acknowledged that South Africa has an existing body of law in delict that deals with injury and harm. It provides a mechanism of compensation for an aggrieved party. Delict involves the standard of negligence in certain cases and that is pinned on a reasonable man test. However, would this test be the best fit given the changes in law? If an AI causes harm or damage the standard of the hypothetical reasonable man would not suffice. In South Africa, AI and the development of computer systems to perform tasks usually requiring human intelligence is progressing. However, as AI improves our everyday life, it also raises human anxiety and concern. The law needs to play catch up to this rapid and growing change in technology. In South Africa there is no legislation dealing specifically with AI and its legal issues that follow. Given the context that the discussion of AI and the law is a mammoth task to undertake, this note focuses only on the aspect of the reasonable man test in the law of delict and how the law can adapt or modify itself in respect of developing AI and cases of harm that are caused by an AI system in delict. The note firstly examines the historical reasonable man test in South Africa and further unpacks the concept of AI. The note further examines and discusses the implications that AI has in respect of delict. The current legislative framework in South Africa is highlighted. In addition, this note examines the international changes made in respect of delict or tort law in respect of AI. Finally, the note provides recommendations as to how South Africa can position itself in respect of delict and AI.